Alcohol and tobacco influencing prevalence of hypertension among 15-54 years old Indian men: An application of discriminant analysis using National Family Health Survey (NFHS), 2015-16 - Jeetendra Yadav; Shaziya Allarakha; Chander Shekhar; Ganesh Prasad Jena (Elsevier, 2021)
Background: Hypertension has been described as an "iceberg disease" as those who suffer are usually unaware and hence usually seek healthcare services at a very late stage. It is estimated that more than two million Indians are suffering from hypertensive heart diseases that contributed to above 0.13 million deaths in 2016. Objectives: The present study aims to know the prevalence of Hypertension in India and its variation by socioeconomic backgrounds, and to find out risk factors discriminating hypertension with special emphasis on tobacco and alcohol consumption among men aged 15-54 years in India. Methods: In this study, NFHS (2015-16) data were analyzed by applying binary logistic regression and discriminant analysis in the attempt to find significant predictors and discriminants of interest. Results: The prevalence of hypertension was 16.5% in the study population. The results suggested that the consumption of alcohol and tobacco are significant discriminant characteristics associated with hypertension irrespective of the socioeconomic background characteristics of the respondents. Hypertension is a chronic disease and is itself a causative factor for several other diseases like renal impairment, other cardiovascular diseases, and stroke. Conclusions: The findings are expected to have direct implications on public health interventions and policy formulation to reduce diseases caused by tobacco and alcohol, particularly hypertension among men in the potential economically productive age group in India and similar settings.